2017
DOI: 10.2134/jeq2017.01.0011
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Role of Soil Texture in Vapor Intrusion from Groundwater Sources

Abstract: Soil texture is believed to play a significant role in the migration of subsurface volatile chemicals into buildings at contaminated sites, an exposure process known as vapor intrusion (VI). In this study, we investigated the role of soil texture in determining the attenuation of contaminant soil gas concentration from groundwater source to receptor building. We performed soil column experiments, numerical simulations, and statistical analysis of the USEPA’s VI database. The soil column experiments were conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 26 publications
1
26
0
Order By: Relevance
“…Due to such complexity, a full 3‐D finite element model is used to study the influences of such a preferential pathway on both of these measures. The 3‐D numerical model applied here was developed with COMSOL Multiphysics and has been presented in previous publications (Bozkurt et al, 2009; Pennell et al, 2009; Yao et al, 2011, 2012, 2013a, 2013b, 2013c, 2015, 2017a, 2017b). The numerical model includes two modules, Darcy's law and chemical transport in porous media.…”
Section: Methodsmentioning
confidence: 99%
“…Due to such complexity, a full 3‐D finite element model is used to study the influences of such a preferential pathway on both of these measures. The 3‐D numerical model applied here was developed with COMSOL Multiphysics and has been presented in previous publications (Bozkurt et al, 2009; Pennell et al, 2009; Yao et al, 2011, 2012, 2013a, 2013b, 2013c, 2015, 2017a, 2017b). The numerical model includes two modules, Darcy's law and chemical transport in porous media.…”
Section: Methodsmentioning
confidence: 99%
“…Governing Equations. A 2D numerical model is built to investigate the influence of groundwater table fluctuations on vapor intrusion using a finite element code COMSOL Multiphysics, which has been widely adopted in previous studies to solve the problem of vapor transport from the contaminant source to the dwelling through the building foundation crack (e.g., [30][31][32][33]). The development and use of this code to solve typical vapor intrusion problems have been described in detail in Pennell et al [30].…”
Section: Numerical Modelingmentioning
confidence: 99%
“…To examine a more realistic VI scenario, Yao et al (2017b) used a 3D numerical model to investigate soil texture's role in determining the attenuation of contaminant soil gas concentration from groundwater source to receptor building. They found that, although soil particle texture can play a role in deciding subslab‐to‐indoor air concentration attenuation, there is no obvious relationship between soil particle size and groundwater source‐to‐subslab attenuation factor except in the case of a shallow contaminant source.…”
Section: Transport In the Vadose Zone: Chlorinated Compoundsmentioning
confidence: 99%